Generating Hope in Group Counseling Through the Meaning of Life in Middle School Adolescents - Melva Syahrial; Neviyarni S; Netrawati (Journal Of Psychology, Counseling And Education, 2024)
Adolescence is a transition period marked by physical, emotional and psychological changes. One of the tasks of teenagers is to accept themselves and have confidence in their abilities. Teenagers need social support at school from teachers and friends. Social support that teenagers can receive directly at school is group counselling activities. In group counselling activities, teenagers can learn about many things together with their teachers and friends. Group counselling as a bridge between students and teachers to discuss problems felt by teenagers. One thing teenager can learn is about generating hope. The hope that teenagers have will make them have enthusiasm in living their days. Hope can be raised by making sense of life. The meaning of life that teenagers understand will make teenagers feel useful. The desire for a meaningful life that drives a person to want himself to be a valuable person for himself and in society. The meaning of life begins with a vision of life, hope and is the reason why individuals must continue to live.